(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, an equality is established for tempered fractional integrals. With the help of this equality, we prove several corrected Euler-Maclaurin-type inequalities for the case of differentiable convex functions involving tempered fractional integrals. Moreover, we provide our results by using special cases of obtained theorems.